Basic provisions of international classifications as criteria for evaluating the health status of rehabilitation of persons with disabilities - E.V. Makarova (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to justify the need for the use of the main provisions of international classifications to determine the state of health improved and effective rehabilitation of persons with disabilities. Material : analyzed more than 50 sources of literature and international instruments on the main provisions of international classifications. Results : conducted a thorough analysis of the content of international classifications. Scientifically substantiated the need for their use in the practice of physical rehabilitation of persons with disabilities. Identify important issues methodically theoretical security goals and objectives of certain types of rehabilitation for persons with disabilities. Subject of discussion questions remain concerning the evaluation criteria of life and human health, the very structure of the rehabilitation process. At the present stage there is scientific and methodological basis of the formation of a new modern tools for determining the conditions of human health arising from the disability. The principles laid down in the international classifications reflect the goals and objectives of rehabilitation, in particular physical rehabilitation of persons with disabilities. Conclusions : these classifications can be successfully used effectively in the process of assessing the level of life and human health, as well as the very structure of the rehabilitation process. Use of certain elements of the international classifications significantly increase efficiency in the provision of rehabilitation assistance to persons with disabilities and improve the methodological approaches to the use of physical rehabilitation.